Enterococcus faecium EF137V: a new strategic source for the control of human and animal health against Campylobacter species (Research, Society and Development, 2020)
The probiotic is related to a food supplement, while the live biotherapeutic products - LBPs are considered biological medicines, both contain living microorganisms with active substances that benefit the host. Enterococcus faecium has many interesting and functional properties for human and animal health, including the antimicrobial capacity, which helps in food poisoning diseases such as Campylobacteriosis. Campylobacter jejuni and C. coli species have been described in this context. Therefore, due to the need to develop alternatives to ensure the safety of products consumed by the population, this work proposes a complementary strategy to reduce or eliminate Campylobacter through the use of Enterococcus faecium EF137V, isolated from artisanal “Coalho” cheese from Pernambuco-Brazil. The analyzes were performed in vitro. Given the adverse conditions, such as acid pH and the presence of bile salts, in which EF137V was exposed, it was found that the bacteria showed resistance to gastrointestinal conditions, adherence to epithelial cells, antimicrobial activity by its metabolic compounds against reference strains of C. jejuni and C. coli, as well as antagonistic activity, which suggests that both species will not be able to grow disorderly in the host's intestinal microbiota, thus being able to control these microorganisms in the bacterial community in broilers and preventing new infections in humans. It can be concluded that the EF137V is a promising PVB and probiotic, presenting great capacity for biotechnology applications.